Research cells as means of promoting academic publication in undergraduate professors - Vázquez Parra, José Carlos (2018)
One of the aspects that more importance is taking in the evaluation of the quality of the universities, is the contribution and the work that these do in investigation. However, it is useless to carry out research processes if they are not disseminated through appropriate publication channels, since there is a risk that the contribution is ignored and really has little or no impact on the problems of the reality and the environment. Therefore, this article seeks to present the results of the generation and implementation of a research group within an academic department of a Mexican private university, demonstrating that with a five-step model, it is possible to detonate the academic production of its teachers.